2013
DOI: 10.1017/s0029665113001286
|View full text |Cite
|
Sign up to set email alerts
|

Feeding the immune system

Abstract: A well-functioning immune system is key to providing good defence against pathogenic organisms and to providing tolerance to non-threatening organisms, to food components and to self. The immune system works by providing an exclusion barrier, by identifying and eliminating pathogens and by identifying and tolerating non-threatening sources of antigens, and by maintaining a memory of immunological encounters. The immune system is complex involving many different cell types distributed throughout the body and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
204
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(229 citation statements)
references
References 153 publications
3
204
0
10
Order By: Relevance
“…Additionally, EPA and DHA exert anti-inflammatory effects following their selective incorporation into the phospholipid fraction of cell membranes where they can act to decrease the signaling efficiency of protein complexes in lipid rafts [70], or serve as substrates for the synthesis of anti-inflammatory bioactive lipid mediators ( i.e. , eicosanoids) [71,72]. Taken together, n -3 PUFA may beneficially modulate obesity-associated pro-inflammatory paracrine interactions between the different cell types within AT.…”
Section: N-3 Polyunsaturated Fatty Acids and Obesitymentioning
confidence: 99%
“…Additionally, EPA and DHA exert anti-inflammatory effects following their selective incorporation into the phospholipid fraction of cell membranes where they can act to decrease the signaling efficiency of protein complexes in lipid rafts [70], or serve as substrates for the synthesis of anti-inflammatory bioactive lipid mediators ( i.e. , eicosanoids) [71,72]. Taken together, n -3 PUFA may beneficially modulate obesity-associated pro-inflammatory paracrine interactions between the different cell types within AT.…”
Section: N-3 Polyunsaturated Fatty Acids and Obesitymentioning
confidence: 99%
“…Several studies have shown that malnourished individuals are frequently more susceptible to infections and present an increased mortality rate [1,2]. Considerable evidence suggests that PM impairs immune functions and affects hematopoiesis, thymic development, and the blood cell count as well as many other immunological parameters [1][2][3][4][5][6]. PM induces structural changes in the lymphoid organs, resulting in the involution of the thymus, lymph nodes, and the spleen.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The transition from a diet of human milk and/or infant formula to a diet consisting of cow' s milk, nonmilk beverages, and solid foods may compromise a child' s nutritional status. 3 Much of the current understanding of nutritional impact on immune outcomes derives from animal studies, which are easily controlled for specific dietary components or from populations whose nutrient deficiencies are endemic.…”
mentioning
confidence: 99%